Phytometabolite profiling of Coronil, a herbal medicine for COVID‐19, its identification by mass‐spectroscopy and quality validation on liquid chromatographic platforms. Issue 22 (29th September 2021) - Balkrishna, Acharya; Tomer, Meenu; Verma, Sudeep; Joshi, Monali; Sharma, Priyanka; Srivastava, Jyotish; Varshney, Anurag
Abstract: Coronil is a tri‐herbal medicine consisting of immunomodulatory herbs, Withania somnifera, Tinospora cordifolia, and Ocimum sanctum . The formulation has been developed specifically as the supporting measure for COVID‐19. Current investigation is aimed to identify the phytoconstituents in Coronil utilizing ultra‐performance liquid chromatography–mass spectrometry coupled with quadrapole time of flight and to establish its quality standardization using high‐performance liquid chromatography and high performance thin layer chromatography. Out of 52 identified compounds, cordifolioside A, magnoflorine, rosmarinic acid, palmatine, withanoside IV, withanoside V, withanone, betulinic acid, and ursolic acid were quantified in 15 different batches of Coronil on validated high‐performance liquid chromatography method. Similarly, withanoside IV, withaferin A, magnoflorine, palmatine, rosmarinic acid, and ursolic acid were analyzed on high performance thin layer chromatography. Methods were validated as per the International Council for Harmonization guidelines. These methods were specific, reproducible, accurate, precise, linear ( r 2 > 0.99), and percent recoveries were within the prescribed limits. The content uniformity of Coronil was ascertained using Fourier transform infrared spectroscopy. Results indicated that, validated methods were fit for their intended use and the analytical quality of Coronil was consistent across the batches. Taken together, these developed methods could drive the analytical quality control of herbal medicines such as Coronil, and other formulations containing similar chemical profiles.